ROBOCOP (ROBOtic Care of Poststroke Pain): Study Protocol for a Randomized Trial to Assess Robot-Assisted Functional and Motor Recovery and Impact on Poststroke Pain Development - Pignolo, Loris; Tonin, Paolo; Nicotera, Pierluigi; Bagetta, Giacinto; Scuteri, Damiana (Frontiers in Neurology, 2022)
Background. Stroke is one of the most frequent causes of death and disability worldwide. It is accompanied by impaired motor function of the upper extremities in over 69% of patients up to hemiplegia in the following 5 years in 56% of cases. This condition often is characterized by chronic post-stroke pain, difficult to manage, further worsening quality of life. Post-stroke pain occurs within 3-6 months. Robot-assisted neurorehabilitation using the Automatic Recovery Arm Motility Integrated System (ARAMIS) has proven efficacy in motor function recovery exploiting the movements and the strength of the unaffected arm. The rationale of the ROBOCOP (ROBOtic Care of Post-stroke pain) randomized trial is assessment of the impact of robot-assisted functional and motor recovery on the prevention of post-stroke pain. Methods. A total of 118 patients with hemiplegic arm due to stroke will be enrolled and randomly allocated with 1:1 ratio to ARAMIS or conventional neurorehabilitation group. After a baseline screening at hospital discharge, ARAMIS or conventional rehabilitation will be performed for 8 weeks. The primary endpoint is prevention of the development of post-stroke pain and the secondary endpoints are prevention of spasticity and efficacy in clinical motor rehabilitation. The primary outcome measures consist in the visual analogue scale (VAS) and in the doleur neuropatique 4 (DN4) and the secondary outcome measures include: the Modified Ashworth Scale (MAS) and the Resistance to Passive movement Scale (REPAS); the Upper Extremity Subscale of the Fugl–Meyer Motor Assessment (FMA-UE); the Action Research Arm Test (ARAT); the Barthel Index (BI) for activities of daily living and the magnetic resonance imaging (MRI) recovery-related parameters. After baseline, both primary and secondary outcome measures will be performed in the following time points: 1 month after stroke (t1, half of rehabilitation); 2 months after stroke (t2, after rehabilitation); 3 months (t3) and 6 months (t4) after stroke, critical for post-stroke pain development. Discussion. This is the first clinical trial investigating the efficacy of robot-assisted neurorehabilitation using ARAMIS on post-stroke pain prevention. This study could remarkably improve the quality of life of stroke survivors. Trial registration. Calabria Region Ethics Committee protocol N.244 of 09/21/2021.